Association of rosuvastatin and delirium in severe sepsis with acute respiratory distress syndrome - Pourafkari, Leili; Nader, Nader D.; Porhomayon, Jahan (Journal of Thoracic Disease, 2016)
Delirium is described as a constellation of clinical manifestations characterized by disruption of consciousness along with alteration in cognition (1,2). It occurs in up to 80% of critically ill patients in intensive care unit (ICU) and is associated with negative clinical and economic consequences (3). Therefore preventive strategies to reduce the occurrence of delirium in ICU are highly appealing for health care professionals.